Intersecting violence: Representations of Somali youth in the Canadian press. (July 2021) - Jiwani, Yasmin; Al-Rawi, Ahmed
This article examines the press coverage accorded to Canadian youth of Somali origin in the Canadian press using two methodological procedures. Charting the representational clusters that cohere around Canadian Black male youth of Somali heritage reveals the circulation of stereotypical tropes that are mostly circumscribed within the framework of crime, terrorism, and violence, reflecting the intersection of stereotypes commonly ascribed to Muslims and to Black males. In the case of the Canadian Somali youth, this representation encompasses major narratives such as 'radicalization and terror', 'immigration and belonging', 'surveillance and safety', and 'gang violence' and, to a lesser extent, positive stories. To corroborate the first level of analysis, the computational analyses reveal four main topics and associations that are similar to the above findings, providing insight into the way Canadian Somali youth, especially men, are facing different challenges in their lived experiences in Canada.